Antibiotic-Prescribing Habits in Dentistry: A Questionnaire-Based Study - Luca Sbricoli; Giulio Grisolia; Edoardo Stellini; Christian Bacci; Marco Annunziata; Eriberto Bressan (MDPI AG, 2024)
The problem of antibiotic resistance is becoming increasingly serious worldwide due to uncontrolled prescription. Dentists are among the groups that prescribe the most antibiotics, often to delay urgent treatment. The purpose of the present study is to investigate the prescribing protocols adopted by dentists for prophylaxis and antibiotic therapy in major clinical surgical indications. Methods: A ten-question survey was administered to a group of Italian dentists. The participants were asked about their preferences for antibiotic administration for the prevention of infective endocarditis, the administration of antibiotics to patients allergic to penicillin, the insertion of implants, and the extraction of third molars. The retrieved data were screened and analyzed. Results: A total of 298 surveys were filled out. The most-prescribed antibiotic was amoxicillin or amoxicillin with clavulanic acid or macrolides for allergic patients. The administration of two grams of amoxicillin one hour before surgery was the most widely used prescriptive protocol for prophylaxis. International guidelines on antibiotic prophylaxis for infective endocarditis were only partially followed. The most heterogeneous results emerged for prophylaxis associated with dental implants or provided prior to surgical third-molar extraction. Conclusions: The present study shows widespread antibiotic prescriptive heterogeneity among the sample of dentists analyzed, especially in conditions where international guidelines are lacking. An evidence-based consensus on prescriptive modalities in dentistry would be desirable in the near future.